Mass spectrometric analysis of heavy and base oils - Heininen, Juho (2018)
Base oil production from crude oil has become more complex as demanded product properties, yield objective and field competition have increased interest in research towards high viscosity index (VI) base oils. Conventional lubricant grade base oil enjoyed biggest market share until 2000-2004 but now high VHVI product demands have introduced also novel production methods for heavy-type base oils such as Ficsher-Tropsch method based gas-to-liquid (GTL) and poly-internal-olefin (PIO) base oils. In this MSc, different mass spectrometric methods for heavy and base oils where compared and in-house field ionization method was characterized and method validation was begun. Base oil mass analytics uses mainly Fourier transformation ion cyclotron resonance (FT-ICR) and sector mass analyzers with soft ionization methods as well as novel ambient ionization (AI) methods. While heaviest asphaltenes compounds require resolutions that are achievable only by FT-ICR instruments majority of petroleum studies including quantitative fraction studies can be done with more cost-efficient and operator-friendly sector and Orbitrap instruments. Novel AI methods are arguably fastest expanding area of mass spectrometry and provide interesting field to follow also for petroleum analysis.